A prática pedagógica alfabetizadora e a formação do Pacto Nacional de Alfabetização na Idade Certa (PNAIC) - Julioti, Sueli (2016)
This research aimed to analyze the pedagogical practice of the teachers of literacy based on the formation of the National Pact for Literacy at the Right Age (PNAIC). The specific objectives are the following: identify whether there were changes in pedagogical practices of the teachers of literacy after their participation in the formation of PNAIC and see which subjects the teachers would add to the formation. We seek to answer the following questions: Were there changes in pedagogical practices of the teachers of literacy after their participation in the formation of PNAIC? Which one? The changes, if they occurred, make it possible to improve the literacy process? What subjects the teachers would add to the formation? Our hypothesis is that the formation conducted by PNAIC promotes changes in teaching practice because it is an area constituted dialogically, therefore, developer of reflection on the praxis, ideological and methodological concepts. The research was conducted in a public school located in the eastern of São Paulo/SP City. The subjects are six, which five are teachers who teach in the literacy cycle and participated in the training and one is a pedagogical coordinator, advisor in training. The methodology used was a qualitative approach and the data collection instrument were semi-structured interviews and observation as well as analysis of the official documents that rule the the present Pact. Data analysis was based on content analysis proposed by Bardin (2011). The research was based on the following authors: Soares (2003), Leal (2005), Ferreiro (1985), Freire (2015) to support the literacy category; Nóvoa (1999), Mortatti (2006), Sacristán (2008), Gatti (2015) to support the formation of teachers category. As results we found that: a) the PNAIC constitutes a necessary intervention for the Brazilian educational context and presents implementation strategies and well-designed partnerships; b) in general, course participants teachers and advisors, considered the PNAIC quite valid because it offers a consistent theoretical and practical instrumentalisation and has contributed to the improvement of pedagogical practice in literacy classes; c) the Pact focuses on the specific and limited aspect (continuing education for teachers in literacy and mathematics) and emphasizes the teaching work in an individual action perspective. The conclusion is that the PNAIC is a necessary measure but not sufficient for an effective promotion of the quality of education, which requires a number of other actions that go beyond the continuing education for teachers, such as: the collective literacy work in the school, the valorisation of education professionals, adequate infrastructure to schools, stimulus for the construction of curriculum proposals with the participation of teachers, the existence of consistent educational projects in educational networks and in schools, the use of the results obtained through evaluations for planning intervention strategies with the participation of public schools, among other measures.